GENDER DALAM NOVEL HABIS GELAP TERBITLAH TERANG KARYA ARMIJN PANE DAN IMPLIKASINYA TERHADAP PEMBELAJARAN SASTRA DI SMA - Sasmayunita Sasmayunita; Dewi Al Aisah (Universitas Khairun, 2021)
The purpose of this study is to describe gender inequality and the characterizations contained in the novel Habis Gelap Terbitlah Terang by Armijn Pane. The method used is a descriptive method with a qualitative approach. The objectives of the research are gender inequality and the characterizations in the novel Habis Gelap Terbitlah Terang by Armijn Pane published by Balai Pustaka. Content analysis techniques were applied to analyze the data. The result of the research shows that: 1) the marginalization of women is contained in the novel Habis Gelap Terbitlah Terang by Armijn Pane. 2) women's subordination, 3) stereotypes of women who obey customs, and 4) stereotypes that place women's position in a weak place. In addition, the research results obtained in this study are in the form of a study of the characters in the novel, which can be divided into several types of naming based on the angle from which the naming was done. A character can be categorized by several types of naming at once. From the results of the analysis, it can be concluded that the characterizations are more emphasized on the female main character, namely R.A Kartini, While the additional characters occupy the minority portion. However, the figures who accept the form of gender injustice are R.A Kartini, M. Ngasirah, Kardinah, and Rukmini. In the female figures, the injustices received are in the form of marginalization, subordination, stereotypes, and violence against women.